(untitled) (REMUNOM, 2025)
Endometritis is the main cause of reduced fertility in mares, in addition to generating major economic and productive losses in equine farming. The accumulation of fluid in the uterine cavity of the mare after insemination is considered normal due to the physiological cleaning reaction developed by the animal itself, in order to eliminate dirt and semen, recognized by the body as a foreign body, preparing the uterus for the installation of the embryo. This process must occur within a period of 24 to 72 hours. Therefore, if this period is exceeded, the accumulation of fluids causes damage to the reproductive health of the animal, causing persistent endometritis, which can evolve into more serious cases such as degenerative endometriosis, excluding the animal from reproduction. Endometritis is the main cause of infertility in mares, and the 3rd leading pathology in horses. The objective of this study was to carry out a systematic review on the subject, showing the main clinical signs, diagnosis and treatment, demonstrating its importance for the reproductive health of mares.